Colombia : the economic foundation of peace - Lafourcade, O.; Giugale, Marcelo; Luff, Connie, 1953- (Washington, DC : World Bank, 2003)
This work offers a synthesis of the development challenges that the incoming president of Colombia is likely to face as well as possible policy responses. The aim of the text is to trigger and support policy debate in Colombia at a historic juncture.
Includes bibliographical references.
oif 16/07/14
Loan
Keywords: Sustainable development -- Colombia; Violence -- Economic aspects -- Colombia; Colombia -- Economic policy